PENGARUH KUALITAS LAYANAN, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI KEPUASAN PELANGGAN DI PERUSAHAAN ALAT KESEHATAN - Rizki Karunia Fajarwati; Wendra Hartono (Bajang Institute, 2026)
This study aims to analyze the influence of service quality, price, and location on repurchase decisions, with customer satisfaction as a mediating variable at PT. X, a medical device distributor in Surabaya. This study used a quantitative design with a survey method of 115 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to assess the direct and indirect relationships between variables. The results showed that service quality, price, and location had a positive and significant influence on customer satisfaction. Furthermore, customer satisfaction had a positive and significant influence on repurchase decisions, acting as the primary mediating variable. While price had a direct influence on repurchase decisions, service quality and location influenced repurchase decisions indirectly through customer satisfaction. This indicates that improving service quality and location optimization alone will not directly drive repeat purchases without contributing to customer satisfaction.